Design formulas for plastics engineers. - Rao, Natti S. (Hanser ; Hanser Gardner Publications [distributor], 2004)
"This book presents a summary of the most important formulas and their applications to solve design and processing problems with plastics materials. Numerous practical examples guide the reader step-by-step through the computational routine of designing polymer machinery. The approach is unassuming and very practical to enable every engineer to apply these concepts in their daily work and improve their equipment and stabilize their processes."--Jacket.